Probing the functions of friedelane‐type triterpene cyclases from four celastrol‐producing plants. (25th November 2021) - Lu, Yun; Luo, Yunfeng; Zhou, Jiawei; Hu, Tianyuan; Tu, Lichan; Tong, Yuru; Su, Ping; Liu, Yuan; Wang, Jiadian; Jiang, Zhouqian; Wu, Xiaoyi; Chen, Xiaochao; et al.
SUMMARY: Triterpenes are among the most diverse plant natural products, and their diversity is closely related to various triterpene skeletons catalyzed by different 2, 3‐oxidosqualene cyclases (OSCs). Celastrol, a friedelane‐type triterpene with significant bioactivities, is specifically distributed in higher plants, such as Celastraceae species. Friedelin is an important precursor for the biosynthesis of celastrol, and it is synthesized through the cyclization of 2, 3‐oxidosqualene, with the highest number of rearrangements being catalyzed by friedelane‐type triterpene cyclases. However, the molecular mechanisms underlying the catalysis of friedelin production by friedelane‐type triterpene cyclases have not yet been fully elucidated. In this study, transcriptome data of four celastrol‐producing plants from Celastraceae were used to identify a total of 21 putative OSCs. Through functional characterization, the friedelane‐type triterpene cyclases were separately verified in the four plants. Analysis of the selection pressure showed that purifying selection acted on these OSCs, and the friedelane‐type triterpene cyclases may undergo weaker selective restriction during evolution. Molecular docking and site‐directed mutagenesis revealed that changes in some amino acids that are unique to friedelane‐type triterpene cyclases may lead to variations in catalytic specificity or efficiency, thereby affecting the synthesis of friedelin. Our research explored the functional diversity of triterpene synthases from a multispecies perspective. It also provides some references for further research on the relative mechanisms of friedelin biosynthesis. Significance Statement: Twenty‐one 2, 3‐oxidosqualene cyclases (OSCs) from four celastrol‐producing plants of Celastraceae were isolated and nine of them were identified as friedelane‐type triterpene cyclases, which could catalyze the conversion of 2, 3‐oxidosqualene into friedelin, β ‐amyrin, and α ‐amyrin. Among them, friedelin is an important precursor for the biosynthesis of celastrol. Through molecular evolution analysis, molecular docking, and site‐directed mutagenesis, our study provides some references for further research on the mechanisms underlying friedelin biosynthesis.